Analysis of the Pematang Siantar City Government's Financial Report From the Perspective of Government Accounting Standards - Gress Sitompul; Irawan Irawan; Dito Aditia Darma; Ayu Kuria Sari (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to analyze the financial statements of the Pematang Siantar City Government for the 2020–2024 period in terms of the application of Government Accounting Standards (SAP) and assess regional financial performance through effectiveness, efficiency, and fiscal independence ratios. This study uses a quantitative descriptive approach with secondary data in the form of the Pematang Siantar City Regional Government Financial Report (LKPD) for 2020– 2024. Data analysis techniques used include regional financial ratio analysis and analysis of the suitability of financial statement presentation based on Government Regulation No. 71 of 2010 concerning Government Accounting Standards. The results of the study indicate that the implementation of SAP in the Pematang Siantar City Government has generally been carried out in accordance with the provisions, but there are still several weaknesses in the aspects of effectiveness and efficiency of regional financial management. The level of effectiveness of Regional Original Revenue (PAD) shows fluctuations and tends to decrease in certain years, while the level of regional spending efficiency is still not optimal. In addition, the level of regional fiscal independence is still relatively low, reflecting a high dependence on transfer funds from the central government. This study is expected to serve as evaluation material for regional governments in improving the quality of financial management as well as the transparency and accountability of regional financial reports. Keywords: Government Accounting Standards, Regional Financial Statements, Effectiveness, Efficiency, Fiscal Independence